Grit and business survivability among small business during the COVID-19 pandemic: The moderating role of servant leadership - Sahat Aditua Fandhitya Silalahi; Akhmad Junaidi; Lokot Zein Nasution; Agung Sutoto; Adi Suryo Hutomo; Joko Sutrisno; Amos Lukas; Josep Ginting; Suripto Suripto; Resanti Lestari (Cogent Business & Management, 2023)
The Covid −19 pandemic has caused businesses to experience a sharp revenue decline due to lockdown policies. It takes resilience and effective leadership to steer businesses through this period of uncertainties. This paper examines how servant leadership (SL) moderates the relationship between grit facets (comprising of the perseverance of effort (PE) and the consistency of interest (CI) among Small and Medium Enterprises (SMEs) business survival (BS) during the COVID-19 pandemic. This study employed a cross-sectional survey method with a purposive sampling method toward employees from 425 SMEs located in West Java, the province hosting Indonesia's highest number of SMEs. The questionnaire items were adapted from previous studies to encompass the variables in question effectively. The partial least square was employed in data analysis, revealing that PE positively affects BS (p = 0.012). The SL approach also strengthens the positive influence of PE on SME BS (p = 0.018). Theoretically, this study contributes to filling the gaps in the entrepreneurship literature involving grit and leadership types (in this context, servant leadership). Specifically, the results demonstrate how SL strengthens the grit characteristics in fostering SMEs" resilience during crises. On the practical front, the findings provide insights for entrepreneurs to utilize the SL approach to enhance the SMEs" resilience during the crisis. Additionally, the results offer policy recommendations to the Government to foster the development of SL and grit character among SMEs. This approach produces longer-lasting impacts and decreases reliance on governmental aid.
Keywords: 650; business survival; Covid-19; grit; servant leadership; small business